2019
DOI: 10.3390/md17080462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Characteristics and Fibril Formation Ability of Collagens Extracted from the Skin of Farmed River Puffer (Takifugu obscurus) and Tiger Puffer (Takifugu rubripes)

Abstract: Acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC) from the skin of river puffer (ASC-RP and PSC-RP) and tiger puffer (ASC-TP and PSC-TP) were extracted and physicochemically examined. Denaturation temperature (Td) for all the collagens was found to be 25.5–29.5 °C, which was lower than that of calf skin collagen (35.9 °C). Electrophoretic patterns indicated all four samples were type I collagen with molecular form of (α1)2α2. FTIR spectra confirmed the extracted collagens had a triple-helical struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
5
6
0
Order By: Relevance
“…The thermal denaturation temperatures of ASC and PSC from red stingray skin were 23.82 °C and 24.46 °C, respectively (Figure 5A). These values were similar to collagens from the swim bladders of miiuy croaker (T d = 24.7 °C, ASC; 26.7 °C, PSC) [35], the skins of tiger puffer (T d = 28.0 °C, ASC; 25.5 °C, PSC) [36], and of Axenillidae (T d = 24.3 °C) [4], but lower than the skins of giant croaker (T d ≈ 34.5 °C, ASC; 34.5 °C, PSC) [37] and of river puffer (T d = 29.5 °C, ASC; 27.5 °C, PSC) [36]. Furthermore, these values were higher than those for the skins of pacific cod (T d = 14.5 °C, ASC; 16.8 °C, PSC) [8] and Spanish mackerel (T d = 15.12 °C, ASC; 14.66 °C, PSC) [38].…”
Section: Resultssupporting
confidence: 59%
“…The thermal denaturation temperatures of ASC and PSC from red stingray skin were 23.82 °C and 24.46 °C, respectively (Figure 5A). These values were similar to collagens from the swim bladders of miiuy croaker (T d = 24.7 °C, ASC; 26.7 °C, PSC) [35], the skins of tiger puffer (T d = 28.0 °C, ASC; 25.5 °C, PSC) [36], and of Axenillidae (T d = 24.3 °C) [4], but lower than the skins of giant croaker (T d ≈ 34.5 °C, ASC; 34.5 °C, PSC) [37] and of river puffer (T d = 29.5 °C, ASC; 27.5 °C, PSC) [36]. Furthermore, these values were higher than those for the skins of pacific cod (T d = 14.5 °C, ASC; 16.8 °C, PSC) [8] and Spanish mackerel (T d = 15.12 °C, ASC; 14.66 °C, PSC) [38].…”
Section: Resultssupporting
confidence: 59%
“…The FT‐IR spectra of BSC and BC exhibited an absorption ratio around 1 between the amide III vibration and the band corresponding to C−N stretching vibrations of pyrrolidine rings from 1449 cm −1 , [29] which indicated the triple helix conformation presence. All these results indicated that the secondary and tertiary structure of BSC analyzed by FT‐IR spectroscopy were similar to those of other marine collagens extracted from salmon, codfish, river puffer and tiger puffer [28–30] . As compared to BC, BSC preparation presented a shift of amide A and amide B bands towards lower frequencies, showing lower structural order of the latter.…”
Section: Resultssupporting
confidence: 57%
“…It was previously showed that the thermal stability of collagen isolated from fish skin was clearly influenced by water temperature [9] . Thus, the Td of collagen isolated from most fish species displayed values below 37 °C [28] . It was documented that, at temperatures higher than Td, the triple helix of collagen molecule was dissociated into a random coil structure, affecting its physicochemical, mechanical and biological properties [12] .…”
Section: Resultsmentioning
confidence: 99%
“…The Td of miiuy croaker swim bladders for ASC= 24.7 ºC and PSC =26.7 ºC) [44]. The Td of tiger puffer skin for ASC =28 ºC and PSC =25.5 ºC [45] respectively. But lower than the Td of Nile tilapia skin (35.2 ºC, ASC) [31].The Td of river puffer skin for ASC = 29.5 ºC, PSC= 27.5 ºC [45].Also, according to Li et al 2013 [46], the collagen of land animal had a higher denaturation temperature than that fish collagen due to its higher amino acid content.…”
Section: Denaturation Temperature (Td)mentioning
confidence: 99%
“…The Td of tiger puffer skin for ASC =28 ºC and PSC =25.5 ºC [45] respectively. But lower than the Td of Nile tilapia skin (35.2 ºC, ASC) [31].The Td of river puffer skin for ASC = 29.5 ºC, PSC= 27.5 ºC [45].Also, according to Li et al 2013 [46], the collagen of land animal had a higher denaturation temperature than that fish collagen due to its higher amino acid content. Chen et al, 2019 [43] showed that the hydrogen bond in the collagen molecule was destroyed when the temperature rises therefore the triple helix structure dissociates then converts into random coil.…”
Section: Denaturation Temperature (Td)mentioning
confidence: 99%